Biodiversity, ecology, and taxonomy of sediment-dwelling Dendrophylliidae (Anthozoa, Scleractinia) in the Gulf of Thailand - Mehrotra, Rahul; Chavanich, Suchana; Monchanin, Coline; Jualaong, Suthep; Hoeksema, Bert W (Contributions to zoology (Amsterdam, Netherlands : 1995), 2023)
Abstract Dendrophylliidae represents one of the most speciose families of scleractinian coral, expressing a wide range of morphological and ecological traits. Recent phylogenetic analyses of the family have indicated that several conventional genera are in need of revision. In the Gulf of Thailand, dendrophylliids are predominantly found on hard-substrate reefs and pinnacles, or on soft-substrate habitats. Soft-substrate habitats in the Gulf of Thailand have been shown to host unique species assemblages and faunal ecology. Here we provided an updated phylogenetic hypothesis for the Dendrophylliidae based on newly sequenced species, and analyses integrating morphology, genetics and ecology. High-resolution Micro-ct was used to create digital versions of the studied species, allowing for non-destructive examination of internal and external features. Our findings allowed for a taxonomic assessment of the genera Heteropsammia and Tubastraea, with the species Balanophyllia (Eupsammia) stimpsonii, moved to the genus Tubastraea. They also support the polyphyly of Dendrophyllia and Cladopsammia. In-situ surveys provided population-density information for four dendrophylliid species from soft substrate habitats, indicating that the species Heteropsammia moretonensis may be the most widespread within the Gulf of Thailand. These surveys also provided novel ecological documentation associated with these corals, including protocooperative feeding upon a sea pen by Tubastraea stimpsonii comb. nov., and feeding upon other cnidarians by Heteropsammia spp.